The tumbling rotational state of 1I/'Oumuamua. (May 2018) - Fraser, Wesley; Pravec, Petr; Fitzsimmons, Alan; Lacerda, Pedro; Bannister, Michele; Snodgrass, Colin; Smolić, Igor
Abstract The discovery1 of 1I/2017 U1 (1I/'Oumuamua) has provided the first glimpse of a planetesimal born in another planetary system. This interloper exhibits a variable colour within a range that is broadly consistent with local small bodies, such as the P- and D-type asteroids, Jupiter Trojans and dynamically excited Kuiper belt objects2–7 . 1I/'Oumuamua appears unusually elongated in shape, with an axial ratio exceeding 5:1 (refs1, 4, 5, 8 ). Rotation period estimates are inconsistent and varied, with reported values between 6.9 and 8.3 h (refs4–6, 9 ). Here, we analyse all the available optical photometry data reported to date. No single rotation period can explain the exhibited brightness variations. Rather, 1I/'Oumuamua appears to be in an excited rotational state undergoing non-principal axis rotation, or tumbling. A satisfactory solution has apparent lightcurve frequencies of 0.135 and 0.126 h−1 and implies a longest-to-shortest axis ratio of ≳5:1, although the available data are insufficient to uniquely constrain the true frequencies and shape. Assuming a body that responds to non-principal axis rotation in a similar manner to Solar System asteroids and comets, the timescale to damp 1I/'Oumuamua's tumbling is at least one billion years. 1I/'Oumuamua was probably set tumbling within its parent planetary system and will remain tumbling well after it has left ours. The brightness variations of the interstellar object 1I/'Oumuamua observed during six nights are incompatible with a unique rotation rate, indicating that the body is tumbling. Colour measurements suggest a heterogeneous surface, with a large red region.